The relationship between the level of anti-diabetic medication adherence and fasting blood glucose levels among patients with type II diabetes mellitus at RSUD Subang - Luthpiah, Nazla; Adiutama, Novian Mahayu; Fauziah, Wardah (Indonesian Nursing Journal, 2023)
Background: Diabetes mellitus is known as the "mother of all diseases" because of the many complications it causes. One effort that can be made to reduce these complications is to control blood glucose levels by maintaining adherence to medication. Purpose: To analysis relationship between anti-diabetic medication adherence and fasting blood glucose level in patients with type II diabetes mellitus. Method: This cross-sectional studied was conducted on 69 patients with type II diabetes mellitus who were recruited used a purposive sampling technique at RSUD Kabupaten Subang. Data collection on adherence anti-diabetic medication was carried out used MMAS-8 and Easy Touch GCU was used to collect data fasting blood sugar levels. The collected data were analyzed used the Spearman's rho test. Result: The findings of this study showed that the average level of adherence to taking anti-diabetic medication was 4.56 and the average fasting blood glucose level in type II diabetes mellitus patients was 176.13 mg/dL. This study founded that there is a relationship between the level of adherence to taking anti-diabetic medication and fasting blood glucose level in patients with type II diabetes mellitus (p <0.001) with a positive correlation coefficient, the greater the medication adherence score, the more normal the fasting blood glucose level, Conclusion: Medication adherence has significantly a relationship with fasting blood glucose level in patients with type II diabetes mellitus. Findings suggest that it is important to adhere to anti-diabetic medication for patients with type 2 diabetes, as it potentially enables patients to deal with their diabetes journey and requires further research.